2015
DOI: 10.5209/rev_clac.2015.v63.50175
|View full text |Cite
|
Sign up to set email alerts
|

La adquisición del tiempo-aspecto en español en L3 para los aprendices taiwaneses

Abstract: Este trabajo tiene como fin investigar el desarrollo de los tiempos pasados en la interlengua de los aprendices taiwaneses que aprenden español como segunda lengua extranjera. El análisis se basa en la Hipótesis de Aspecto Léxico que se centra en la importancia del aspecto léxico de los verbos. Llegamos a las siguientes conclusiones:(1) los aprendices taiwaneses de español cuya lengua materna es chino-mandarín manejan el pretérito mejor que el imperfecto en la producción escrita de los niveles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 1 publication
1
6
0
2
Order By: Relevance
“…According to the distribution of correct uses for different lexical aspects (stative and dynamic verbs), the results showed the overall accuracy rate 12 of preterit usage to be higher than that of imperfect usage by Taiwanese learners of Spanish in spoken production for both levels, 56.57% > 45.97% for the beginning level 13 , and 58.56% > 54.28% for the intermediate level 14 . The same tendency was observed in the early stage of Taiwanese learners' written production, 84.75% > 61.42% for the beginning level (Lu et al, 2015). This has also been found to be the case for English-native speakers of Spanish (cf.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…According to the distribution of correct uses for different lexical aspects (stative and dynamic verbs), the results showed the overall accuracy rate 12 of preterit usage to be higher than that of imperfect usage by Taiwanese learners of Spanish in spoken production for both levels, 56.57% > 45.97% for the beginning level 13 , and 58.56% > 54.28% for the intermediate level 14 . The same tendency was observed in the early stage of Taiwanese learners' written production, 84.75% > 61.42% for the beginning level (Lu et al, 2015). This has also been found to be the case for English-native speakers of Spanish (cf.…”
Section: Resultssupporting
confidence: 76%
“…The accurate use of the imperfect for beginning and intermediate levels in the stative verbs was 52.22% and 66.62%, which were higher than the accuracy rates for the dynamic (38.81% and 46.85%), activity (39.87% and 49.53%), and telic (21.59% and 24.07%) verbs. Based on a written task (Lu et al, 2015), the comparison of the results for the current study using oral data and the results of an earlier study using the written data are shown in Figure 1 Authors, 2015), the comparison of the results for the current study using oral data and the results of an earlier study using the written data are shown in The accuracy rate was calculated by dividing the total of correct uses by student number.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…La mayor parte de los estudios realizados con sinohablantes en Español como Lengua Extranjera (ELE) se centran en aprendices de edad adulta y muy especialmente en un contexto universitario (Cortés 2002;Sánchez Griñán 2008;Martínez y Marco 2010;Lu 2015;Agüero 2016, etc. ); este es el primer estudio de ELE con sinohablantes en edad escolar.…”
Section: Introductionunclassified